CURRICULUM VITAE: A DISCOURSE OF CELEBRATION WITH NARCISSISTIC ALLUSIONS - Yazid Basthomi (TEFLIN, 2012)
The present study, a part of a larger project, deals with the under-researched (sub) genre of curriculum vitae (CV) of theses written in English by Indonesian students of English as a foreign language (EFL). The corpus was composed of CV of 40 theses obtainable from the Graduate Library, Graduate Program, Universitas Negeri Malang (State University of Malang), Indonesia. In a categorical structure, the CVs exhibit four main issues: personal information about age and familial origin, academic information pertaining to educational backgrounds, work information, and another piece of personal information, i.e., family. Central to the findings is that the CVs allude to the notion of celebration with narcissistic expressions.